2011
DOI: 10.1007/s12665-011-1119-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability of trace metals in suspended matter of the Mandovi estuary, central west coast of India

Abstract: Studies on the suspended particulate matter (SPM) in the Mandovi estuary, western India indicate that during the monsoon and pre-monsoon, the SPM increases, and the major and trace metals decrease from stations in the upstream to downstream of the estuary. SPM is consistently low at all stations during the post-monsoon. Trace metals (Cu, Ni, Zn, Cr, and Pb) show strong inter-relationships. They correlate well with Fe and Mn only during the monsoon. The concentrations of Cr, Cu, and Pb are high during the post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The moderate pollution of Fe and Mn in sediment cores is directly related to Fe-Mn ore deposits and humaninduced activity in handling and transportation of these ores through the river. Shynu et al (2012) and Alagarsamy (2006) also observed a high value of Fe and Mn in suspended matter and surface sediments, respectively in the Mandovi river. The moderate contamination of Cu and Cr might be associated with the presence of boatyard and small vessel building yards.…”
Section: Contaminationmentioning
confidence: 79%
“…The moderate pollution of Fe and Mn in sediment cores is directly related to Fe-Mn ore deposits and humaninduced activity in handling and transportation of these ores through the river. Shynu et al (2012) and Alagarsamy (2006) also observed a high value of Fe and Mn in suspended matter and surface sediments, respectively in the Mandovi river. The moderate contamination of Cu and Cr might be associated with the presence of boatyard and small vessel building yards.…”
Section: Contaminationmentioning
confidence: 79%
“…Monthly rainfall data and total sunshine was obtained from the Meteorological Station, Goa. Temperature, salinity and chlorophyll- a (Chl a ) data were obtained from the Data Centre of National Institute of Oceanography (CSIR), Goa, while total suspended solid (TSS) data is from Shynu et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Around 15 million t of iron and manganese ore was transported annually along these rivers to the nearby Mormugao harbor in 1990′s (Satyanarayana and Sen Gupta, 1996) which increased to around 50 million t in 2010′s. The ore stored for transportation at different points on the shores of the estuary gets eroded and flushed into the estuaries during heavy monsoon rains and part of the ore and/or dust ultimately gets accumulated in the estuaries and is incorporated into sediment (Shynu et al, 2012;Alagarsamy, 2006. Iron ore was mined from the banded iron formations of Goa, India, and transported through the Mandovi and Zuari estuaries for six decades until the ban on mining from September 2012.…”
Section: Study Areamentioning
confidence: 99%